TO THE HISTORY OF THE PUBLISHING HOUSE "RECORD" BY MYKOLA KOVALIUK - Vasylchuk, Mykola (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
The article examines the activities of the Kolomyia publisher of the interwar period, Mykola Kovaluk. This is the first study to highlight the work of the publishing house he founded, "Record", outline the subject matter and repertoire of publications, and analyze the publishing policy. The author of the article uses advertising materials for analysis, which he considers as a self-characteristic of the publisher. The thematic scopes of the main book series of the publishing house "Record" and periodicals of Mykola Kovaluk are outlined. The meaning of one of the publications of "Record" - a dictionary of foreign words by Oleksa Skalozub is revealed.